2012
DOI: 10.1007/s00535-012-0637-5
|View full text |Cite
|
Sign up to set email alerts
|

Metformin protects against lipoapoptosis and enhances GLP-1 secretion from GLP-1-producing cells

Abstract: This study demonstrates that metformin protects against lipoapoptosis (possibly by blocking JNK2 activation), and enhances GLP-1 secretion from GLP-1-producing cells in vitro. These direct effects of the drug might explain the elevated plasma GLP-1 levels seen in diabetic patients on chronic metformin therapy. The findings may also be harnessed to therapeutic advantage in efforts aiming at enhancing endogenous GLP-1 secretion in type 2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 28 publications
2
46
1
1
Order By: Relevance
“…The mechanisms of action explaining why metformin may promote GLP-1 secretion from L cells are rather complex 84 . A recent study demonstrated that metformin protects against lipoapoptosis (possibly by blocking JNK2 activation), and enhances GLP-1 secretion from GLP-1-producing cells in vitro 85 . These direct effects of the drug might explain the elevated plasma GLP-1 levels seen in diabetic patients on chronic metformin therapy 81 .…”
Section: Potential Synergistic Activitymentioning
confidence: 99%
“…The mechanisms of action explaining why metformin may promote GLP-1 secretion from L cells are rather complex 84 . A recent study demonstrated that metformin protects against lipoapoptosis (possibly by blocking JNK2 activation), and enhances GLP-1 secretion from GLP-1-producing cells in vitro 85 . These direct effects of the drug might explain the elevated plasma GLP-1 levels seen in diabetic patients on chronic metformin therapy 81 .…”
Section: Potential Synergistic Activitymentioning
confidence: 99%
“…Protein samples from cells were prepared for Western blot analysis using a modified RIPA buffer, and Western blot was performed as described previously [26]. Immunoblot analyses were performed using antibodies that recognize phosphorylated ERK 1/2, total ERK 1/2, phosphorylated p38 MAPK, total p38 MAPK, phosphorylated JNK, total JNK, phosphorylated eNOS and total eNOS (Cell Signaling Technology, Danvers, Mass., USA), pS239-VASP (16C2 [27]) and VASP (AB19728 [28]).…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have been designed to investigate effects of this on L-cells and whether lipotoxicity occurs also in these cells. In a series of recent studies, cells of the GLUTag cell line were exposed to simulated hyperlipidaemia using the saturated fatty acid palmitate, the most abundant saturated fatty acid in serum [121,184,185]. This resulted in increased DNA fragmentation and caspase-3 activity in conjunction with reduced viability of GLP-1-producing cells [121,184,185].…”
Section: Lipotoxicity and Glp-1mentioning
confidence: 97%